Intersectionality Squared: Intrastate Minimum Wage Preemption & Schuette’s Second-Class Citizens - Johnson, Alexsis M. (Columbia Journal of Gender and Law, 2018)
Between 2012 and 2017, more than twenty municipalities passed ordinances providing for extended labor protections for their residents like paid sick leave and higher minimum wages. Often these municipalities and their governing bodies have been more liberal and racially diverse than their respective legislatures. In some of the states where municipalities have succeeded in passing this legislation, the state legislature has very quickly preempted those measures with a state law dictating that no city can set a minimum wage higher than the federal standard of 7.25 an hour. These state laws banning cities from raising the working wage constitute intrastate minimum wage preemption. The lawmakers preempting these local reform efforts proffer to justifications for the bills rooted in economics and federalism. However, these preemptive measures raise consequential questions related to the due process of lawmaking and equal protection jurisprudence more generally. This Note applies an intersectional analysis to the ongoing conservative strategy of intrastate minimum wage preemption6 to reveal one example of how such preemptive measures limit progressive change, and especially burden Black women and women of color. Ultimately, this Note identifies two significant phenomena—or “intersections”— that, together, amount to what this Note will call Intersectionality Squared.